1988
DOI: 10.1002/1097-4679(198803)44:2<131::aid-jclp2270440207>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Affects, demographic variables, and health

Abstract: The revised Multiple Affect Adjective Check List (MAACL‐R) was given to a national probability sample that consisted of 1,543 adults who also were interviewed, which provided demographic data and self‐ratings of health, medication use, and social activities. Standardization procedures have reduced markedly the acquiescence factor and the correlations among the dysphoric affect scales in the MAACL‐R. The demographic variables of sex, race, age, education, occupation, income, marital status, religion, geographia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…A possible confounding variable, however, is physical health status. It is likely, because of the definition of assisted living, that this group had lower physical health status, and there is evidence of a relationship between physical health and depressive mood (Davis-Berman, 1988; Lubin et al, 1988;Numan, Barklind, & Lubin, 1981).…”
Section: Resultsmentioning
confidence: 98%
“…A possible confounding variable, however, is physical health status. It is likely, because of the definition of assisted living, that this group had lower physical health status, and there is evidence of a relationship between physical health and depressive mood (Davis-Berman, 1988; Lubin et al, 1988;Numan, Barklind, & Lubin, 1981).…”
Section: Resultsmentioning
confidence: 98%
“…For example, given our older sample, several variables tapping health were included -namely, perceptions of one's health, physical symptoms, physical functioning, severity of pain, and energy level. Research has demonstrated a consistent relationship between poor health status and unhappiness and distress, especially in older people (Lubin et al, 1988;Okun et al, 1984; for reviews, see Pressman and Cohen, in press). However, other studies have found that when other factors are taken into account, subjective health status has little effect on happiness levels (see Diener, 1994).…”
Section: The Present Studymentioning
confidence: 91%
“…Second, age influences the proactive behavior displayed to receive external stimulation. Sensation or experience seeking decreases with age (Gross et al , 1997; Lubin et al , 1988; Steinberg et al , 2008) because younger individuals search for stimuli that produce excitement and emotions (Costa and McCrae, 1986). They are more change-oriented and carry less conservative propensities (Zuckerman, 1979).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…emotion in retailing, Loureiro and Roschk, 2014); and emotion in advertisement, Drolet et al , 2007; McKay-Nesbitt et al , 2011; Williams and Drolet, 2005) and studies on the relationship between age and brand attachment are scarce and focused on adolescents (Bidmon, 2017) or perfume brands (Lambert-Pandraud and Laurent, 2010). Because age influences how individuals experience affect (Birditt and Fingerman, 2003; Diener et al , 1985; Lawton et al , 1992) or display proactive behavior to external stimulation (Gross et al , 1997; Lubin et al , 1988; Steinberg et al , 2008), further attention to the role of age on the relationship between brand experience and brand attachment is warranted. Knowing what consumer age groups are more prone to attach to experiential brands will allow managers to segment the market and better manage consumer behavior.…”
Section: Introductionmentioning
confidence: 99%